Hubungan Antara Husnudzon dengan Kecemasan Sosial pada Remaja Pengguna Media Sosial di Bukittinggi - Zuliana Wijaya (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
In this study, teenage social media users in Bukittinggi are asked to examine the connection between social anxiety and husnudzon, or optimistic thinking. Purposive sampling was used to choose 114 teenagers, ages 15 to 19, who then took part in survey design. Positive thinking and social anxiety levels were assessed using standardized questionnaires, the Husnudzon Scale and the Social Anxiety Scale for Adolescents, respectively. Product moment analysis was used in the data analysis. Higher levels of positive thinking are linked to lower levels of social anxiety, according to the research, which showed a substantial negative association between husnudzon and social anxiety. Husnudzon's role as a strong predictor of social anxiety was further validated by multiple regression analysis, which also helped to explain a large variation in the participants' social anxiety levels.